HUBUNGAN PENGETAHUAN GIZI DAN KEBIASAAN KONSUMSI FAST FOOD DENGAN BODY IMAGE PADA SISWA PUTRI - Lestari, Puji; Elian Devina, Kezia; Ria Gita, Anggi Putri (Ensiklopedia of Journal, 2026)
Adolescent girls are in a transitional period from childhood to adulthood marked by lifestyle changes. Lack of knowledge leads to frequent fast-food consumption and unhealthy eating habits. The desire for an ideal body also drives strict diets and negative body image perceptions. This study aims to analyze correlation between nutrition knowledge and fast-food consumption with body image in female adolescents. This is observational study with cross-sectional design. 35 respondents were selected with purposive random sampling. Nutrition knowledge was collected using the questionnaire, fast food consumption collected with Food Frequency Questionnaire (FFQ) and Body image were using Figure Rating Scale (FRS). Data were collected was analyzed with Rank Spearman. There was correlation between nutrition knowledge with body image (p=0,003). There was no correlation between fast food consumption with body image (p=0,14). There was a significant correlation between nutrition knowledge with body image but there was no correlation between fast food consumption with body image.Keywords: Adolescents Girl, Body Image, Fast Food Consumption, Nutrition Knowledge